Mucosal inflammation at the respiratory interface: a zebrafish model - Progatzky, Fränze (Am J Physiol Lung Cell Mol Physiol, 2015)
Inflammatory diseases of the respiratory system such as asthma and chronic obstructive pulmonary disease are increasing globally and remain poorly understood conditions. Although attention has long focused on the activation of type 1 and type 2 helper T cells of the adaptive immune system in these diseases, it is becoming increasingly apparent that there is also a need to understand the contributions and interactions between innate immune cells and the epithelial lining of the respiratory system. Cigarette smoke predisposes the respiratory tissue to a higher incidence of inflammatory disease, and here we have used zebrafish gills as a model to study the effect of cigarette smoke on the respiratory epithelium. Zebrafish gills fulfill the same gas-exchange function as the mammalian airways and have a similar structure. Exposure to cigarette smoke extracts resulted in an increase in transcripts of the proinflammatory cytokines TNF-α, IL-1β, and MMP9 in the gill tissue, which was at least in part mediated via NF-κB activation. Longer term exposure of fish for 6 wk to cigarette smoke extract resulted in marked structural changes to the gills with lamellar fusion and mucus cell formation, while signs of inflammation or fibrosis were absent. This shows, for the first time, that zebrafish gills are a relevant model for studying the effect of inflammatory stimuli on a respiratory epithelium, since they mimic the immunopathology involved in respiratory inflammatory diseases of humans.